(3Lfi GdCRgGQ ef GdQhV GdeYWGQ aj YLGFH GdCbWGQs - (3TgGH GdOjf CMeO Hf Ydj Hf YHO GdbGOQ GdebQjRis; (3eMeO Hf eMeO Hf YHO Gddg Hf YHO GdefYe Hf YHO GdfhQ, CHh YHO Gddg GdMejQj,J (B900 (3g` ? s
(3ChdgG (B:s
(3hHYO adeG cGf cJGH GdQhV GdeYWGQ ai YLGFH GdCbWGQ ef CMSf eG Ufa s
(3BNQgG (B:s
(3eQShfg HdO cHjQI ef HdGO GdQhSjI hLGeYI YGeQI CgdgG eMHhS s
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjIs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B53s
Keywords: (3GdLZQGajG h GdHdOGfs